Coin-Collecting Northern India - Rodgers, Charles J. (Brill | Manohar Publishers & Distributors, 2024)
Coin-Collecting in Northern India is a numismatic study covering the entire Northern India. Plates are depicted by the author to study Pali, Indo-Greek, and Indo-Roman coins during the ancient period. Coins unearthed from Kashmir from the era of Hindu kingdoms to Sultanate kingdoms are also discussed in detail. The Delhi Sultanate, Mughal, Suri, and post-Mughal era coins are also studied in this book.